Differential expression of miRNAs revealed by small RNA sequencing in traumatic tracheal stenosis - Li, Wentao; Wei, Jinmei; Huang, Pingping; Wei, Yuhui; Chang, Li; Liu, Guangnan (Frontiers in Genetics, 2024)
Introduction: Traumatic tracheal stenosis (TTS) is a major cause of complex difficult airways, without clinically definitive efficacious drugs available. This study was aimed at providing a general view of interactions between micro and messenger ribonucleic acids (miRNAs and mRNAs) and many potential mechanisms in TTS via small RNA sequencing. Methods: In this study, the identification of miRNAs was completed by use of small RNA sequencing and samples from four TTS patients and four normal control cases. By using bioinformatics tools miRanda and RNAhybrid for identifying the candidate target genes of miRNAs with differential expression in each sample, Gene Ontology and Kyoto Encyclopedia of Genes and Genomes were employed for enriching the predicted target genes of miRNAs with differential expression based on the correspondence between miRNAs and their target genes. We detected the expression of the candidate miRNAs using real-time quantitative polymerase chain reaction (qRT-PCR). Results: Twenty-four miRNAs with significant differential expression were identified, including 13 up-regulated and 11 down-regulated ones. Bioinformation technology was adopted to predict 2,496 target genes. These miRNA-target genes were shown to be primarily enriched in cells and organelles with catalytic activity and binding function, such as binding proteins, small molecules and nucleotides. Finally, they were observed to process into TTS through the intercellular and signal regulation of related inflammatory signaling and fibrosis signaling pathways. QRT-PCR confirmed the up-regulation of miR21-5p and miR214-3p and the down-regulation of miR141-3p and miR29b-3p, which was expected to become a high-specific miRNA for TTS. Conclusions: Among all the miRNAs detected, 24 miRNAs demonstrated differential expression between TTS and normal control groups. A total of 2,496 target genes were predicted by bioinformation technology and enriched in inflammatory and fibrotic signaling pathways. These results provide new ideas for further studies and the selection of targets for TTS in the future.